2008
DOI: 10.1111/j.1365-2133.2008.08611.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of protoporphyrin IX synthesis to photodynamic effects by 5-aminolaevulinic acid and its esters on various cell lines derived from the skin

Abstract: PpIX production by ALA and its esters was induced on both normal and malignant cell lines derived from the skin, and cell death of PDT responses is closely related to the amount of PpIX synthesis rather than to the irradiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…It has been established that the efficacy of PDT is closely related to the amount of PpIX produced in cells, rather than the irradiation dose used. 34,35 Moreover, Moan et al showed that PpIX generation in cells is cell density and cell volume dependent being higher in G2 and M phase in comparison to G1. 36 Another explanation for the discrepancies in phototoxicity results between different cell lines may come from the fact that the photosensitivity of cells is larger in high-density cultures 36 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that the efficacy of PDT is closely related to the amount of PpIX produced in cells, rather than the irradiation dose used. 34,35 Moreover, Moan et al showed that PpIX generation in cells is cell density and cell volume dependent being higher in G2 and M phase in comparison to G1. 36 Another explanation for the discrepancies in phototoxicity results between different cell lines may come from the fact that the photosensitivity of cells is larger in high-density cultures 36 .…”
Section: Discussionmentioning
confidence: 99%
“…ALA was purchased from Sigma (St. Louis, MO, USA). The ALA hexenyl ester (C11H19NO3·HCl, ALA-hx) were made as previously described (18). ALA and ALA-hx were dissolved in serumfree RPMI medium immediately before use.…”
Section: Methodsmentioning
confidence: 99%
“…SGT cells were washed with PBS and incubated in serum-free culture medium containing each photosensitizer of ALA and ALA-hx. Four hours after photosensitizer administration, the cells were exposed with light doses of 5 J/cm 2 of a red light-emitting diode (LED) light with 613-645 nm wavelength, with peak 635 nm (Philips Luxeon Lumileds, San Jose, CA, USA) at 35 mW/cm 2 as measured with a Delta Ohm DO 9721 quantum photo-radiometer and thermometer data logger (model DO9721, Padua, Italy) (18).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations